The contribution of implicit learning and explicit learning to the success of the quality of educational service - chibani, leila; alik, namia (El Omda in Linguistics and Discourse Analysis, 2024)
This research attempts to provide a more dynamic educational environment that relies on knowledge as an essential element, as the element of tacit knowledge and explicit knowledge and the role of each of them in the success of higher education quality have been highlighted, and knowledge is an essential part of the knowledge management process within the educational institution and on the basis of which it can Starting in other businesses gives it a competitive advantage, and the more it is available in any practical organization organized to manage that knowledge and spread it among the employees, the more distinguished and successful it will be.